Pengaruh Kepemimpinan Kepala Desa dan Kompetensi Perangkat Desa Terhadap Kepuasan Masyarakat di Desa Bukit Murau Jambi - Setiawan, Marwan; Aji, Seno; Jumisar; Milasari, Roza (Fakultas Hukum dan Ekonomi Bisnis, 2025)
This study aims to analyze the influence of the village head's leadership and the competence of village officials on community satisfaction in Bukit Murau Village. The research method used is quantitative with a descriptive approach. The data analysis technique employed is multiple linear regression to determine the extent to which the independent variables, namely the village head's leadership and the competence of village officials, affect the dependent variable, which is community satisfaction. The results indicate that the village head's leadership has a significant impact on community satisfaction. Additionally, the competence of village officials also proves to have a significant influence on community satisfaction. Simultaneously, the village head's leadership and the competence of village officials contribute significantly to improving community satisfaction in Bukit Murau Village.